Standardization of Health Informatics – Results and Challenges - Klein, G. O. (Methods of Information in Medicine, 2002)
Objectives: This review article aims to highlight the importance of standards for effective communication and provides an overview of international standardization activities.Methods: This article is based on the experience of the author of European standardization in CEN, which he leads, and the global work of ISO, where he is leading the security working group, and an overview of the work of DICOM, IEEE and HL7, partly using their web presentations.Results: Health communication is highly dependent of the general development of information technology with standards coming from ISO/IEC JTC1, ITU and several other organizations e.g. IETF, the World Wide Web consortium and Open group. A number of standardization initiatives have been in progress for more than ten years with the aim to facilitate different aspects of the exchange of health information. Electronic record architecture, Message structures, Concept representation, Device communication including imaging and Security are the main areas.Conclusions: Important results have been achieved, and in some fields and parts of the world, standards are widely used today. Unfortunately, we are still facing the fact that most healthcare information systems cannot exchange information with all systems for which this would be desired. Either the existing standards are not sufficiently implemented, or the required standards and necessary national implementation guidelines do not yet exist. This causes unacceptable risks to patients, inefficient use of healthcare resources, and sub-optimal development of medical knowledge. Fortunately, the different bodies are now largely co-operating to achieve global consensus.
Keywords: Health informatics; standardization